2016
DOI: 10.1016/j.immuni.2016.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells Exhibit Distinct Features in Human Breast Cancer

Abstract: Summary Regulatory T (Treg) cells reside in lymphoid organs and barrier tissues where they control different types of inflammatory responses. Treg cells are also found in human cancers, and studies in animal models suggest that they contribute to cancer progression. However, properties of human intratumoral Treg cells and those present in corresponding normal tissue remain largely unknown. Here, we analyzed features of Treg cells in untreated human breast carcinomas, normal mammary gland, and peripheral blood.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

71
600
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 546 publications
(695 citation statements)
references
References 44 publications
(42 reference statements)
71
600
1
Order By: Relevance
“…Use of adjacent tumorfree tissue allows identification of tumor-specific, rather than tissue-specific, differences in Tregs and T cells, as discussed previously (34)(35)(36). In addition to showing increased numbers of Tregs in tumors compared with adjacent lung tissue, our study is the first to our knowledge to show tumor-specific increases in Treg numbers within lung LNs, even in early stages, when LNs are free of metastases.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Use of adjacent tumorfree tissue allows identification of tumor-specific, rather than tissue-specific, differences in Tregs and T cells, as discussed previously (34)(35)(36). In addition to showing increased numbers of Tregs in tumors compared with adjacent lung tissue, our study is the first to our knowledge to show tumor-specific increases in Treg numbers within lung LNs, even in early stages, when LNs are free of metastases.…”
Section: Discussionsupporting
confidence: 59%
“…Moreover, we found a negative correlation between Ki67 + expression in Tregs and tumor size, suggesting that along with tumor growth, factors such as hypoxia, nutrient deprivation, and tumor necrosis may impair division of immune cells, including Tregs. A recent study of Tregs in human breast cancer came to a similar conclusion by showing that the TCR repertoires between normal tissue and tumor-associated Tregs did not overlap, suggesting that Tregs are recruited (36).…”
Section: Discussionmentioning
confidence: 69%
“…The classical ligand for CCR8 are CCL1 and CCL18, however it has been shown that CCL17 also induces migration of CCR8-expressing cells 44 , which is relevant in the cancer field as CCL17 has been strongly associated with tumour progression 27 . Same year, two independent research groups also described CCR8 as one of the main chemokine receptor in Tregs present in breast 45 , colorectal and non-small-cell lung cancer 46 . Whereas Plitas et al, mentioned that tumour environment has the ability to potentiate CCR8 expression in Tregs, De Simone et al, discussed that the presence of CCL18 in different tumours might be associated with the migration of CCR8 + cells 45,46 .…”
Section: Regulatory Cd4 + Th-like Helper Cells In Cancermentioning
confidence: 99%
“…Same year, two independent research groups also described CCR8 as one of the main chemokine receptor in Tregs present in breast 45 , colorectal and non-small-cell lung cancer 46 . Whereas Plitas et al, mentioned that tumour environment has the ability to potentiate CCR8 expression in Tregs, De Simone et al, discussed that the presence of CCL18 in different tumours might be associated with the migration of CCR8 + cells 45,46 . In 2017, our research group characterized the presence of Th1, Th2, Th17 and Th1/17 Tregs in peripheral blood and several tissues, such as skin, colon, thymus, spleen and liver perfusates 31 .…”
Section: Regulatory Cd4 + Th-like Helper Cells In Cancermentioning
confidence: 99%
See 1 more Smart Citation